Correlative infrared nanospectroscopic and nanomechanical imaging of block copolymer microdomains - Pollard, Benjamin; Raschke, Markus B. (Beilstein Journal of Nanotechnology, 2016)
Intermolecular interactions and nanoscale phase separation govern the properties of many molecular soft-matter systems. Here, we combine infrared vibrational scattering scanning near-field optical microscopy (IR s-SNOM) with force–distance spectroscopy for simultaneous characterization of both nanoscale optical and nanomechanical molecular properties through hybrid imaging. The resulting multichannel images and correlative analysis of chemical composition, spectral IR line shape, modulus, adhesion, deformation, and dissipation acquired for a thin film of a nanophase separated block copolymer (PS-b-PMMA) reveal complex structural variations, in particular at domain interfaces, not resolved in any individual signal channel alone. These variations suggest that regions of multicomponent chemical composition, such as the interfacial mixing regions between microdomains, are correlated with high spatial heterogeneity in nanoscale material properties.
Keywords: block copolymers, force–distance nanomechanical spectroscopy, hybrid imaging, near-field infrared spectroscopy, scanning probe microscopy